Experimental Evaluation of the Effect of Kagocel on Reproductive Function When Administered in Prophylactic Courses During the Period of Impuberty - T. G. Borovskaya; V. A. Mashanova (Антибиотики и Химиотерапия, 2020)
This article focuses on the experimental study ofreproductive safety of three sequential courses of Kagocel introduced to rats (males, females) during the period of impuberty (from the 10th day to the 45th day of life). The drug was administered in a therapeutic dose (TD) and at a dose exceeding that by 10 times (10TD). When the animals reached the mature age, the rats of the experimental groups were mated with intact partners and with each other. To assess reproductive safety, the fertility index and the embryonic death rates were determined. In the antenatal period of development the weight, the size of the fetuses, sex distribution, the status of their internal organs (Wilson method), and the state of the ossification processes (Dawson method) were determined on the 20th day of pregnancy. The survival index and body mass dynamics were evaluated in the postnatal period. The results of the study showed that all investigated parameters did not differ from those in the control group (placebo, P≤0.017). The received data testify to reproductive safety of prophylactic courses of Kagocel used during all period of impuberty.